Revisiting Justice in Income Tax Article 23 Withholding and Corporate Income Recognition - Julie Ekapuri Widjaja; Shelly Kurniawan (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2026)
Taxpayers operating as corporations are required to maintain proper bookkeeping, which mandates that every transaction be recorded in accordance with the period in which it occurs. Corporations engaged in service provision are subject to withholding of Income Tax (PPh) Article 23 by the income provider at the time of payment for the services rendered. The Withholding Tax Evidence (BUPOT) for PPh Article 23 serves as a tax credit that can be accounted for in the Annual Corporate Income Tax Return (SPT Tahunan PPh Badan). This study aims to examine the legal inconsistencies regarding the withholding period of PPh 23 in relation to the income recognition of corporate taxpayers from the perspective of fairness, while also proposing solutions to address the issues arising from these discrepancies. The methodology employed in this research is a normative legal approach utilizing the statute approach. The findings indicate that the withholding of PPh Article 23 for corporate taxpayers in the service sector can lead to significant overpayment or underpayment of taxes each fiscal year, particularly when gross revenue fluctuates from year to year. Additionally, this study identifies several potential solutions that could be implemented to resolve the various challenges encountered.